Time to first dose of measles-containing vaccine and associated factors among infants in Ethiopia: a survival analysis from performance monitoring for action data - Abeje, Eyob Tilahun; Enyew, Ermias Bekele; Daba, Chala; Asmare, Lakew; Bayou, Fekade Demeke; Arefaynie, Mastewal; Mohammed, Anissa; Tareke, Abiyu Abadi; Keleb, Awoke; Kebede, Natnael; Tsega, Yawkal; Endawkie, Abel; et al. (Frontiers in Public Health, 2025)
IntroductionThe measles-containing vaccine (MCV) is a live attenuated vaccine that helps to develop lifelong immunity, and it prevents measles outbreak when administered at the right time in measles-endemic areas. Many infants received the initial dose of the measles vaccine later than the ideal time frame, and significant others missed the vaccination, causing a recurrent measles outbreak in Ethiopia. This study assessed the time to the first dose of a measles-containing vaccine and associated factors among infants in Ethiopia.MethodsA cohort of 1,770 mother–infant pairs was analysed using data from the performance monitoring for action Ethiopia dataset. Cohort-2 Ethiopian data set was collected in Addis Ababa, Amhara, Oromia and SNNP regions between between November 2021 and August 2023. The key independent variables were socio-demographic characteristics, maternal health service utilization, and pregnancy intention. Multiple imputation was used to handle missing data. Survival analysis was conducted using R programming language version 4.4.1. Multicollinearity was assessed using Generalized variance inflation factors (GVIF), and model fit was evaluated using concordance index and overall model significance.ResultsAmong 1,770 infants followed, only 27% were vaccinated timely, within 9–10 months of age (survival probability = 0.73), and 53.4% had not yet received MCV1 at 12 months of age. The hazard of receiving the first dose of measles vaccine (MCV1) was 35% lower among infants from pregnancies that were not desired at all (AHR = 0.65, 95% CI: 0.46-0.93) and 21% lower among those infants from pregnancies that were initially undesired but later became wanted (AHR = 0.79, 95% CI: 0.65–0.96), compared to infants from pregnancies that were desired from the beginning.ConclusionDespite progress in the uptake of the first dose of measles vaccine, timely vaccination in Ethiopia is still low, and many infants in Ethiopia miss the immunization. Institutional delivery, maternal intention regarding pregnancy, religion, and wealth quantile were key predictors of the timeliness of the first dose of measles vaccine. Interventions encouraging institutional deliveries, supporting unintended pregnancy, working with religious leaders, and conducting continuous outreach to immunization services are necessary to improve the timely uptake of the first dose of measles vaccine.